Disturbance-tolerant primates as sentinels for global health and biodiversity conservation - Kowalewski, Miguel Martin (2018)
Over 60% of known infectious diseases have zoonotic sources with the majority caused by pathogens of wildlife origin. The close phylogenetic relationship between humans and wild primates results in high potential for zoonotic transmission, as evidenced by the global HIV pandemic and Ebola outbreaks in Africa. In many rural areas of the tropics, growing human populations and changes in land use are increasing overlap between humans and wild primates. This includes large-scale activities, such as extractive industries (i.e., logging, mining); as well as small-scale interfaces, such as subsistence use of natural resources, ecotourism, and research. Such changes place people in closer, and often more intimate, contact with wild primates. Conversely, increasingly fragmented habitats force primates to forage more widely for resources, including active use of human dominated systems (i.e., crop raiding of agricultural fields and urban occupation). All of these scenarios have the capacity to increase the risk of zoonotic disease transmission. Some primates that persist in anthropogenically-altered landscapes, such as howler monkeys (Genus Alouatta), are sensitive to many of the same pathogens as humans. Consequently, such resilient species have the capacity to serve as sentinels of ecosystem health and provide an early alert of potential risks to human health. Here we provide an overview of how human-wild primate interaction and overlap can affect zoonotic transmission dynamics and highlight opportunities to mitigate health-related threats to humans and wild primates using disturbance-tolerant primate species as sentinels.